Fostering Interfaith Understanding: Lessons From Kiai Ibrahim And Kerukunan Umat Beragama In Religious And Social Education - Liza Zakiyah; Kurniawan, Eri; Dallyono, Ruswan; Gunawan, Wawan (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
This article delves into the pivotal roles of religious and social education in shaping individual values and fostering societal harmony within Indonesia's multicultural and multi-religious context. Using Iwan Mucipto's novel Kiai Ibrahim and Religious Harmony as a literary lens, the discussion highlights how religious education can promote mutual respect and counteract intolerance and extremism. In contrast, social education cultivates responsible citizenship and social cohesion. Through a qualitative content analysis of the novel, we explore the portrayal of vital Islamic values—akidah (faith), Syariah (law), and akhlak (behavior)—and their interconnection with social values such as empathy, sacrifice, and communal support. The findings underscore the novel's potential as an educational tool, offering insights into holistic development strategies essential for contemporary educational challenges. This study contributes to the ongoing dialogue on integrating moral and social education in diverse societies, emphasizing the urgency of fostering peace and understanding in an increasingly divided world.